2014
DOI: 10.1177/1533317514539376
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Cognitive Training for Individuals With Intellectual and Developmental Disabilities

Abstract: (1) Very high adherence rates (94%) of the sample and 100% of the cognitive training group indicate that when given adequate individual support, adults with ID/DD can successfully use a cognitive stimulation program. (2) No significant between- or within-group effects were observed for cognitive training when a stringent α, corrected for multiple comparisons, was used. (3) Trends of improvement in cognitive function were observed for the cognitive training group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
(39 reference statements)
0
22
0
1
Order By: Relevance
“…The studies of intellectual functioning are addressing skills such as attention and understanding (Rezaiyan et al, 2007), working memory (Delavarian et al, 2015), punctuation and comprehension (Segatto et al, 2017), and cognitive skills (Siberski et al, 2014;Tsimaras et al, 2014). Also, the study regarding performing recycling tasks is included, because the feature of problem solving is mainly presented in the study by Chang et al (2014).…”
Section: Studies Resultsmentioning
confidence: 99%
“…The studies of intellectual functioning are addressing skills such as attention and understanding (Rezaiyan et al, 2007), working memory (Delavarian et al, 2015), punctuation and comprehension (Segatto et al, 2017), and cognitive skills (Siberski et al, 2014;Tsimaras et al, 2014). Also, the study regarding performing recycling tasks is included, because the feature of problem solving is mainly presented in the study by Chang et al (2014).…”
Section: Studies Resultsmentioning
confidence: 99%
“…One recent study examined the effects of computerised cognitive training for individuals with ID across 15 cognitive processes involving 32 adults with ID. Siberski et al (2015) found that the intervention programme was suitable for all participants, with some support needed. Withingroup comparisons found that those in the training group showed trends of improvement on 11 of the 15 cognitive measures promoting the potential that, with support, a cognitive training programme can be used for a population with ID and can help to improve aspects of cognitive functioning.…”
mentioning
confidence: 99%
“…They included preand post-intervention tests of cognitive status and provided sufficient statistical data for the effect assessment of computerized cognitive training platform CogniFit. Over 26 studies were excluded because they focused on participants with multiple sclerosis, intellectual or developmental disabilities as well as older adults with insomnia (Haimov & Shatil, 2013;Siberski et al, 2015;Shatil et al, 2010;Cimermanová & Ram, 2013). Design of the studies All studies were randomized-controlled studies as per the inclusion criteria of the present paper.…”
Section: Resultsmentioning
confidence: 99%